Forget me not : a novel - Willingham, Stacy (Minotaur Books, 2025)
"A pulse-pounding new Southern thriller from the author of the runaway bestseller A Flicker in the Dark. Twenty-two years ago, Claire Campbell's older sister, Natalie, disappeared shortly after her eighteenth birthday. Days later, her blood was found in a car, a man was arrested, and the case was swiftly closed. In the decades since, Claire has attempted to forget her traumatic past by moving to the city and climbing the ranks as an investigative journalist... until an unexpected call from her father forces her to come back home and face it all anew. With the entire summer now looming ahead-a summer spent with nothing to do in her childhood home, with her estranged mother-Claire decides on a whim to accept a seasonal job at Galloway Farm, a muscadine vineyard in coastal South Carolina less than an hour away from where she grew up. At first glance, Galloway is an idyllic escape for Claire. A scenic retreat full of slow-paced nostalgia, as well as a place where her sister seemed truly happy in that last summer before she vanished, it feels like the perfect plan to pass the time. However, as soon as Claire starts to settle in, she stumbles across an old diary written by one of the vineyard's owners, and what at first seems like a story of young rebellion and love turns into something much more sinister as it begins to describe details of various unsolved crimes. As the days stretch on, Claire finds herself becoming more and more secluded as she starts to obsess over the diary's contents... as well as the lingering feeling that her own sister's disappearance may be somehow tied to it all. Galloway was supposed to be a place to help her move forward, but instead, Claire quickly finds herself immersed in her own dark and dangerous past"-- Provided by publisher.